Molecular Evolution of Two Distinct dmrt1 Promoters for Germ and Somatic Cells in Vertebrate Gonads. (6th December 2016) - Mawaribuchi, Shuuji; Musashijima, Masato; Wada, Mikako; Izutsu, Yumi; Kurakata, Erina; Park, Min Kyun; Takamatsu, Nobuhiko; Ito, Michihiko
Abstract : The transcription factor DMRT1 has important functions in two distinct processes, somatic-cell masculinization and germ-cell development in mammals. However, it is unknown whether the functions are conserved during evolution, and what mechanism underlies its expression in the two cell lineages. Our analysis of the Xenopus laevis and Silurana tropicalis dmrt1 genes indicated the presence of two distinct promoters: one upstream of the noncoding first exon (ncEx1), and one within the first intron. In contrast, only the ncEx1-upstream promoter was detected in the dmrt1 gene of the agnathan sand lamprey, which expressed dmrt1 exclusively in the germ cells. In X. laevis, the ncEx1- and exon 2-upstream promoters were predominantly used for germ-cell and somatic-cell transcription, respectively. Importantly, knockdown of the ncEx1-containing transcript led to reduced germ-cell numbers in X. laevis gonads. Intriguingly, two genetically female individuals carrying the knockdown construct developed testicles. Analysis of the reptilian leopard gecko dmrt1 revealed the absence of ncEx1. We propose that dmrt1 regulated germ-cell development in the vertebrate ancestor, then acquired another promoter in its first intron to regulate somatic-cell masculinization during gnathostome evolution. In the common ancestor of reptiles and mammals, only one promoter got function for both the two cell lineages, accompanied with the loss of ncEx1. In addition, we found a conserved noncoding sequence (CNS) in the dmrt1 5ʹ-flanking regions only among amniote species, and two CNSs in the introns among most vertebrates except for agnathans. Finally, we discuss relationships between these CNSs and the promoters of dmrt1 during vertebrate evolution.